Juego simbólico y el desarrollo cognitivo en niños de la institución educativa inicial N°602 San Juan Bautista 2024 - Vasquez Perez, Ninoska (2025)
The purpose of the research is to determine the relationship between the level of application of symbolic play and cognitive development in children of the Institution Educative Initial N°602, San Juan Bautista 2024. The research had a quantitative, relational type, with a correlational design and transectional. The study population was made up of all the children of the Initial Educational Institution No. 602, San Juan Bautista 2024, totaling 95. Observation was used as a technique for data collection and an observation guide was used as an instrument. which were validated by a team of experts in the field. The results obtained given the Spearman's Rho correlation coefficient of 0.846 and the statistical significance of 0.05, it can be concluded that there is a strong and significant relationship between the level of symbolic play and cognitive development in children. This suggests that a higher level of symbolic play is associated with better cognitive development, which supports the importance of encouraging symbolic play in the educational context.